Pengaruh Lingkungan Kerja Dan Work Stress Terhadap Kinerja Karyawan Pada PT. Gading Peruna Citra Enineering Kota Bengkulu - Gunawan, Bobi Candra; Bustami, Taufik (Jurnal Fokus Manajemen, 2024)
This research aims to examine the influence of the work environment and work stress on employee performance at PT Gading Peruna Citra Engineering, Bengkulu City. The research sample is employees of PT. Gading Citra Engineering Bengkulu City. This research uses quantitative methods. The data collection technique in this research uses a questionnaire, which is a data collection technique carried out by giving questions and written statements to respondents to answer. The data analysis techniques used in this research are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, t Test, f Test, Multiple Linear Regression, Determination Coefficient Test using SPSS.Multiple linear regression analysis with hypothesis testing, with the research results it can be concluded that all independent variables, namely variables (Work Environment and Work Stress) simultaneously or together have a significant effect on the dependent variable, namely Employee Performance (Y). This means Ho is rejected and Ha is accepted. It can be concluded that the work environment and work stress together have a significant effect on employee performance at PT. Gading Peruna Citra Engineering Bengkulu City.The conclusion of this research shows that there are two variables that have a significant influence, namely the work environment on employee performance and work stress on employee performance.